2020
DOI: 10.1002/eng2.12085
|View full text |Cite
|
Sign up to set email alerts
|

Design of a wideband square slot bandpass frequency‐selective surface using phase range analysis

Abstract: This article presents the design of a wideband bandpass frequency-selective surface (FSS). The structure is designed using the analysis of the generalized scattering matrix (GSM)-based transmission phase range. A relationship between the transmission phase range and the bandpass fractional bandwidth (FBW) is developed. The analysis reveals that the FBW of the FSS unit-cell is proportional to the phase range. Based on the interpretation of results, a design curve has been drawn, and using this curve, a simple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Phase range is also an important parameter to decide Fractional Bandwidth of FSS. In previous studies it is demonstrated for a square loop based system that FBW is proportional to the change in phase range [17,18]. In this research, a method is developed to predict FBW by tuning simulated phase range ( 2) equal to the analytical phase range ( 1).…”
Section: A Design Simulated For Various Frequenciesmentioning
confidence: 99%
“…Phase range is also an important parameter to decide Fractional Bandwidth of FSS. In previous studies it is demonstrated for a square loop based system that FBW is proportional to the change in phase range [17,18]. In this research, a method is developed to predict FBW by tuning simulated phase range ( 2) equal to the analytical phase range ( 1).…”
Section: A Design Simulated For Various Frequenciesmentioning
confidence: 99%
“…In a recent publication [8], three shapes of the folded slot (Lshape, U-shape, and meandering line) were used for filtering applications. In a recent publication, an FSS structure of a square slot was investigated to relate the bandwidth of transmission with the phase range of the unit cell [15]. A bandpass FSS unit cell composed of two specially designed cavities with mixed electric and magnetic boundaries was presented in [16].…”
Section: Introductionmentioning
confidence: 99%